Pelatihan dan Motivasi Dalam Peningkatan Kinerja Karyawan Cafe di Jakarta Selatan - Hidayat, Candra; Setiawan, Christin; Gantina, Devita (Jurnal Ilmiah Pariwisata, 2020)
Employee performance is the most important aspect in the operations of a company. In maintaining or improving employee performance, activities and plans are required by the HR Department. This study aims to analyze whether training and motivation affect employee performance. This research was conducted in a café located in South Jakarta, the samples were employees wich work in the café. This research applied a quantitative descriptive method with correlation and hypothesis testing. The result confirmed that the training variable has a significant effect on employee performance. Work motivation variable has a positive effect on employee performance. The coefficient value of the work motivation variable is greater than the coefficient of the training variable, indicating that the work motivation variable tends to be more dominant in determining employee performance. Keywords: Employee Performance; Motivation; Training